English-Major Student Reflections on Challenges of Consecutive and Simultaneous Interpretation in an EFL Country - Vu Van, Tuan; Bui Thi Kieu, Giang (Journal of Language Learning and Assessment, 2025)
Purpose Interpretation is a crucial skill for English-major students in EFL countries, particularly as they prepare for professional careers in language services. However, both consecutive and simultaneous interpretation have many difficulties, needing good cognitive, linguistic and memory skills. This study investigated students' perceived difficulty, cognitive load, memory, fluency, accuracy, effectiveness of training, language proficiency, and stress and coping strategies in both modes of interpretation.   Methodology Using a quantitative research approach, data were collected from 125 English-major students through structured Likert-scale questionnaires and performance-based assessments. Statistical analyses, including t-tests and ANOVA, were conducted to identify gender and residence-based differences in interpretation challenges.   Results/Findings The findings reveal that simultaneous interpretation is perceived as significantly more difficult than consecutive interpretation, with students reporting higher cognitive load, more significant mental fatigue, and fluency breakdowns under pressure. Difficulties in memory and note-taking appeared as consistent challenges of consecutive interpretation and stress, as well as confidence in one's own language capacity, affected overall performance. Gender analysis showed that female students rated their linguistic proficiency lower than male students despite similar performance levels.   Implications The study concludes that enhanced cognitive training, fluency-building exercises, stress management techniques, and earlier interpretation training in academic curricula can improve student interpreters' skills. The findings provide insights for developing curriculum and interpretation training programs in EFL contexts.